The effect of training and career development on work achievement - Irwan Nopian Sinaga (Jurnal Mantik, 2023)
The main problem in this study is that low work performance can be caused by a lack of training and development which is considered not optimal. This can be seen from the decline in his performance at PT. Industri Pembungkus Internasional from 2018-2020. Employees do not complete work on time optimally so that their performance decreases. The method in this research is quantitative. The population in this study, namely employees, a sample of 42 respondents. The data sources in this study are primary data and secondary data. While the data analysis technique used is descriptive analysis and multiple linear regression. The results of multiple regression analysis are Y= 1.304 + 0.627X1 + 0.428X2 + e which shows training and career development have a positive and significant effect on work performance. While the results of partial test show that training has a positive and significant effect on work performance, the t-count value is 4.637>t-table 2.022 and the career development variable also has a positive and significant effect on work performance, the t-count value is 3.177>t-table 2.022. The coefficient of determination is 0.688. 68.8% variation of the dependent variable namely training and career development in the model can explain the variable Job Achievement at PT. IPI while the remaining 31.2% is influenced by other variables outside the model.